Design Educational Materials to Upgrade Speech Skills for Middle School Beginners / تصميم المواد التّعليميّة لترقيّة مهارة الكلام للنّاشئين بالمدرسة المتوسّطة - Malia Fransisca (Abjadia, 2019)
This study was based on several language errors in the intensive class student PP MAS Nasyi’in Sidoarjo when speaking Arabic, both in terms of the order in which words and sentences were laid out and the grammar or rules. Therefore, it is necessary to design learning materials to improve speaking skills specifically for intensive class students of the PP MAS “A” group Nasyi’in. The formulation of the problem is: (1) What are the characteristics of the book design of speaking skill learning for intensive class “A” group PP MAS Nasyi’in?, (2) How effective design book learning of speaking skill for intensive classes group “A” of PP MAS Nasyi’in? The objectivitas of this study are: (1) To find out the characteristics of the book design of the speaking skill learning for intensive class  “A” PP MAS Nasyi’in, (2) To find out the effectiveness of the speaking skill learning for intensive class  “A” PP MAS Nasyi’in. The research method is Research and Development (R D). Data collection used was observation, interviews, questionnaires and tests. The tests used in this study were pre-test and post-test. The 6 steps in making this design book are observation, data collection, design of learning material, 1st validation, book experiment and 2nd validation. From the test result tested, the result of the data obtained are as follows: t count 3.67 and t table 2.718. So, if t count is greater than t table then the design of learning is effective. Conversely, if t count is smaller than t table, the learning design is not effective. Thus it can be concluded that the design of the material made by this researcher is considered effective and has an influence in improving the skills of speaking Arabic in intensive class students of the PP MAS “A” group Nasyi’in. The design book has a different character. These characters can be seen from several aspect, including: (1) Learning Material Aspects: The material prepared is the conversation of local material as well as ta’birat al istilahiyyah needed by students, (2) Language Aspect: The language used in this design book is simple, (3) Psycological Aspect: The use of names and images in the design book is nothing but the name of the intensive class students themselves so that it adds to their motivation